The Corpus of Discourses on the COVID-19 Pandemic in Poland: Research Project Assumptions - Duda, Beata; Ficek, Ewa (2022)
The article presents a research project on linguistically profiled (quantitative and qualitative) analyses of the (sub)space of pandemic-related discourses, as well as the corpus of Polish texts concerning the SARS-CoV-2 pandemic that broke out in 2020. The authors describe the following: 1. the reasons for the interest in this issue, the subject and purpose of the research and the research theoretical and methodological background – discourse linguistics (mainly from the perspective of Jürgen Spizmüller and Ingo Warnke); 2. source material of the project (mainly individual/ non-institutional Internet statements that constitute the basis for the shaping of specific systems of meaning, i.e. comments posted under posts on Facebook or Twitter and the dialogical relations among them); 3. problems related to the development of the pandemic discourses corpus (criteria for the selection of texts, methods of the corpus balancing, categories of metadata that shall be used for the material description); 4. conclusions drawn from an exemplary analytical procedure where a section of the corpus was used; 5. the potential of the above-mentioned research and possible applications of the research results.
Keywords: pandemic; discourse; linguistic analysis of discourse; corpus linguistics; corpus of COVID-19 texts